Recent advances in the epidemiology of nonalcoholic fatty liver disease in children. Issue 11 (9th September 2021) - Shapiro, Warren L.; Noon, Sheila L.; Schwimmer, Jeffrey B.
Summary: Children with obesity are at risk for numerous health problems, including nonalcoholic fatty liver disease (NAFLD). This review focuses on progress made in the epidemiology of NAFLD in children for the years 2015–2020. The estimated prevalence of NAFLD in children with obesity is 26%. The incidence of NAFLD in children has risen rapidly over the past decade. An understanding of the reasons for this rise is incomplete, but over the past 5 years, many studies have provided additional insight into the complexity of risk factors, diagnostic approaches, and associated comorbidities. Risk factors for NAFLD are wide‐ranging, including perinatal factors involving both the mother and newborn, as well as environmental toxin exposure. Progress made in the noninvasive assessment will be critical to improving issues related to variability in approach to screening and diagnosis of NAFLD in children. The list of serious comorbidities observed in children with NAFLD continues to grow. Notably, for many of these conditions, such as diabetes and depression, the rates observed have exceeded the rates reported in children with obesity without NAFLD. Recent advancements reviewed show an increased awareness of this problem, while also calling attention to the need for additional research to guide successful efforts at prevention and treatment.